The effect of perceived usefulness, perceived ease of use, and lifestyle on purchase intention - Abidin, Zainal (Universitas Ahmad Dahlan, 2024)
Purpose-Advances in digital technology impact various business activities, such as digital marketing through e-commerce. Digital marketing through e-commerce can expand consumer reach while reducing business operating costs. In digital marketing, each seller will try to attract consumers to buy their products. Many factors certainly influence consumer intention to buy. Therefore, this study aims to determine the effect of perceived usefulness, perceived ease of use, and lifestyle on purchasing intentions in e-commerce users. Design/Methodology/Approach-This study's population consisted of all e-commerce users in Asia, and the sample obtained was 100 people selected based on specific criteria. The data was collected by distributing questionnaires online and measuring them using a Likert scale. The data obtained from respondents was then processed using SPSS software. Findings-Based on the test results, perceived usefulness, perceived ease of use, and lifestyle positively affect the purchase intention of e-commerce users. The perceived usefulness of this study has proven to be positive but insignificant to consumer purchase intentions. This means that perceived usefulness only partially encourages consumer buying intentions because other factors highly influence buying intentions, such as perceived ease of use, lifestyle, and other factors not examined in this study. Research limitations/implications-This research is limited in that the respondents' sample only represents e-commerce users in Asia, so the respondents' answers cannot represent all e-commerce users worldwide. In addition, e-commerce currently circulating is diverse, and this research has not discussed specific e-commerce users, so future research is expected to use specific e-commerce user respondents. Originality/value-Research on the factors that influence purchase intention through e-commerce in Asia still needs to be improved. This research discusses e-commerce users in the Asian region by considering the aspects of perceived usefulness, perceived ease of use, and lifestyle.